TASKS OF STATE POLICY OF THE NATIONAL SECURITY - Yarovoі, Tyhon (Theory and Practice of Public Administration, 2019)
The article is devoted to the scientific research of the problem of defining the tasks of state policy in the field of national security. On the basis of the analysis of studies of foreign and domestic scientists, the current Ukrainian legislation, an attempt was made to identify gaps in national security policy.Considering that the people of Ukraine are the source of power and the bearer of sovereignty, special attention is paid to such components of national security as the protection of national interests and protection of national values. Ukraine’s national interests are defined by a number of regulations, but their understanding is often quite controversial. The situation with national values is even worse. They remain uncertain. Various researchers include religiosity, polyconfessionalism, multi-ethnicity, multiculturalism, family values, territorial integrity, natural environment, scientific-educational and scientific-technical potentials, state sovereignty, cultural and material heritage of the nation. Moreover, a number of scholars consider this state of affairs to be natural and hope that, over time, both national interests and national values will be finally formed.The author does not share such optimism and is convinced of the need for urgent formation of a unified, national vision of national interests and national values, which should be based on relevant scientific research.As a proper example of defending national interests, the author cites the position of Viscount Palmerston, regarding the interests of England, which is a priority in the foreign and domestic policy of the state. Given Ukraine’s European choice, our scholars and politicians should focus on such examples, not on the ideological standarts of the Soviet era.One of the important tools for the formation and implementation of effective state policy in the field of national security, in a democratic state, the author considers the formation of an effective system of regulation of lobbying.